Model Penerimaan QRIS: Studi Pada Mahasiswa di Purwokerto - Pernanda Pramestiani, Angelina; Fitriati, Azmi; Budi Santoso, Suryo; Nur Azizah, Siti (Journal of Accounting and Finance Management, 2025)
This research aims to analyze the factors that influence the intention to use QRIS. QRIS is type of digital payment that is currently popular in Indonesia. The success of using QRIS is determined by the user’s willingness to use this technology. The population of this study were students in Purwokerto who used QRIS. The samples used was 257. The data collection technique uses accidental sampling. The analysis technique uses the SEM-PLS method. The results of this research indicate that perceived transaction convenience has a positive effect on mobile usefulness. perceived transaction speed has a positive effect on mobile ease of use. Perceptions of mobile ease of use, optimisme and personal innovativeness have a positive effect on behavioral intention. And the perception of mobile usefulness has no influence on behavioral intention. The implication of this research is to analyze students’s intentions towards using QRIS and show how QRIS can increase payment efficiency.